Serological evidence of canine leptospirosis in the Kamentsá indigenous community, Putumayo, Colombia - Romero, Marlyn H. (2018)
The objective of this study was to determine the prevalence of canine leptospirosis and identify factors associated with the infection in an indigenous Kamentsá population of the department of Putumayo, Colombia. Blood samples of dogs of both sexes (n=154) located in the rural area of Sibundoy Valley were collected. Demographic, sanitary, and responsible tenure variables were identified through a structured survey. Blood samples were processed by the macroscopic microagglutination test (MAT) using a reference strain collection composed of 24 serogroups of Leptospira serogroups. The prevalence of antibodies against Leptospira sp was 79.9%. The most frequent serogroups were Gripotyphosa (10.2%), Hursbridge (8.4%), Sarmin and Australis (7.2%), Canicola (6.8%) and Tarassovi (6.4%). The associated risk factors were the age of the dog, the presence of sewage and the possession of more than one dog in the house (p<0.05). In conclusion, the high prevalence of antibodies against Leptospira sp in dogs suggests that there is a potential risk of transmission of the bacteria to man and, therefore, it is necessary to strengthen the promotion, prevention and surveillance measures by Public Health authorities.